Animal Population Estimation Using Flickr Images - Menon, Sreejith; Berger-Wolf, Tanya; Kiciman, Emre; Joppa, Lucas; Stewart, Charles V.; Parham, Jason; Crall, Jonathan; Holmberg, Jason; Oast, Jonathan Van (In Proceedings of 2nd International Workshop on the Social Web for Environmental and Ecological Monitoring (SWEEM 2017), 2017)
While the technologies of the Information Age have produced staggering amounts of data about people, they are by and large failing the world’s wildlife. Even the simplest and most critical piece of information, the number of animals of a species, is either unknown or is uncertain for most species. Here, we propose to use images of wildlife posted on social media platforms, together with animal recognitions software and mark-recapture models, to estimate population sizes. We show that population size estimates from social media photographs of animals can produce robust results, yet more work is needed to understand biases inherent in the approach.